2012
DOI: 10.1523/jneurosci.6225-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Antennal Lobe Processing Correlates to Moth Olfactory Behavior

Abstract: Animals typically perceive their olfactory environment as a complex blend of natural odor cues. In insects, the initial processing of odors occurs in the antennal lobe (AL). Afferent peripheral input from olfactory sensory neurons (OSNs) is modified via mostly inhibitory local interneurons (LNs) and transferred by projection neurons (PNs) to higher brain centers. Here we performed optophysiological studies in the AL of the moth, Manduca sexta, and recorded odor-evoked calcium changes in response to antennal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 70 publications
4
39
0
Order By: Relevance
“…OSNs expressing the same receptor, and thus responding to the same set of odorants, converge onto the same glomerulus in the AL (Gao et al, 2000; Vosshall, 2000) as has been demonstrated for Drosophila melanogaster and indirectly also in several moth species (Hansson, 1997). Spatio-temporal patterns of neuronal activity representing sensory input to the AL can be visualized by optical imaging methods (Hansson et al, 2003; Skiri et al, 2004; Carlsson et al, 2005; Silbering and Galizia, 2007) enabling identification of compound- and blend-specific responses in the AL of M. sexta (Hansson et al, 2003; Bisch-Knaden et al, 2012; Kuebler et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…OSNs expressing the same receptor, and thus responding to the same set of odorants, converge onto the same glomerulus in the AL (Gao et al, 2000; Vosshall, 2000) as has been demonstrated for Drosophila melanogaster and indirectly also in several moth species (Hansson, 1997). Spatio-temporal patterns of neuronal activity representing sensory input to the AL can be visualized by optical imaging methods (Hansson et al, 2003; Skiri et al, 2004; Carlsson et al, 2005; Silbering and Galizia, 2007) enabling identification of compound- and blend-specific responses in the AL of M. sexta (Hansson et al, 2003; Bisch-Knaden et al, 2012; Kuebler et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Mapping natural search algorithms onto the MAB framework would constitute a major step toward a quantitative understanding of the similarities and differences between search strategies. Recent studies of the neural and biophysical mechanisms involved in search behavior (6,7,9,10,46,58) provide the quantitative information needed to define such models in a way that respects the constraints on search strategies in real biological systems.…”
Section: Convergent Evolution and Shared Features Of Effectivementioning
confidence: 99%
“…Mayer and his contemporaries, including Jean-Henri Fabre (2), initiated the study of what is now one of the most heavily investigated search algorithms in nature: the olfactory search strategies of insects. Over a century later, studies of how insects and other animals find odor targets have led to major discoveries about the structure and information contained within chemical plumes (3)(4)(5) and the properties of the nervous system that allow animals to extract and respond to that information in a complex and ever-changing landscape (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Furthermore, olfactory information is significantly modulated by a dense network of local neurons in the first olfactory center of the insect brain, the antennal lobe (AL) (reviewed in Galizia and Rössler, 2010;Masse et al, 2009;Wilson, 2013;Wilson and Mainen, 2006). Nevertheless, physiological odor mixture responses in the AL are qualitatively predictable on the basis of mixture constituent responses in Drosophila (Olsen et al, 2010;Silbering and Galizia, 2007) and other insects (Carlsson et al, 2007;Deisig et al, 2006;Deisig et al, 2010;Fernandez et al, 2009;Joerges et al, 1997;Stierle et al, 2013; but see Anton and Hansson, 1996;Kuebler et al, 2011;Kuebler et al, 2012;Meyer and Galizia, 2012). Therefore, if single OSN class responses are already behaviorally meaningful, the innate hedonic valence of odor mixtures may in fact be predictable on the basis of the valences of mixture constituents.…”
Section: Introductionmentioning
confidence: 99%